The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/dta.3055
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a fast ultra‐high‐performance liquid chromatography tandem mass spectrometry method for determining carbonic anhydrase inhibitors and their metabolites in urine and hair

Abstract: A new, rapid, sensitive, and comprehensive ultra-high-performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method for quantifying diuretics (acetazolamide, brinzolamide, dorzolamide, and their metabolites) in human urine and hair was developed and fully validated. Twenty-five milligrams of hair were incubated with 500-μl M3 ® buffer reagent at 100 C for 1 h for complete digestion. After cooling, 1-μl supernatant was injected onto chromatography system. Urine samples were simply diluted befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…With respect to the concentrations already published for subjects under treatment with diuretics, 18–20 the measured concentrations are much lower. However, during two anti‐doping violations, Gheddar et al identified hydrochlorothiazide at 6–15 pg/mg in the head hair of a rugby player 21 and at 36 pg/mg in the head hair of a top athlete 20 who challenged his adverse analytical finding, demonstrating that in athletes, the diuretic concentrations can be much lower to the ones measured in clinical patients.…”
Section: Acetazolamide Concentrationsmentioning
confidence: 82%
See 3 more Smart Citations
“…With respect to the concentrations already published for subjects under treatment with diuretics, 18–20 the measured concentrations are much lower. However, during two anti‐doping violations, Gheddar et al identified hydrochlorothiazide at 6–15 pg/mg in the head hair of a rugby player 21 and at 36 pg/mg in the head hair of a top athlete 20 who challenged his adverse analytical finding, demonstrating that in athletes, the diuretic concentrations can be much lower to the ones measured in clinical patients.…”
Section: Acetazolamide Concentrationsmentioning
confidence: 82%
“…Identification in hair of acetazolamide has been very recently published by Lo Faro et al 18 The authors measured 2300 pg/mg in the hair of a subject treated daily with acetazolamide for systemic hypertension. However, diuretic detection in hair has been seldom reported.…”
Section: Acetazolamide Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test was still positive, with an approximate dorzolamide concentration of 0.5 ng/ml. The urine concentration of subjects treated for ocular disease 22 are much higher (a magnitude of 100)…”
Section: Resultsmentioning
confidence: 99%